AKUMULASI BAHAN KERING DAN INDEKS KLOROFIL BIBIT KAKAO AKIBAT APLIKASI AIR KELAPA DENGAN KONSENTRASI BERBEDA - Santi Rosniawaty; Cucu Suherman; Mochamad Arief Sholeh; Rija Sudirja; Dimas Nur Annisa (Jurnal Agroekoteknologi, 2021)
Cocoa seedling are plant material to be planted in the field, superior seedling can produce maximum cocoa pods. Good cacao seeds can be produced from superior cultivar, one of the superior cultivar was the ICCRI 08H cultivar. Fertilization was required so that the cocoa seeds can grow perfectly. The fertilizer was used usually inorganic fertilizers, there was an alternative to fertilizing using coconut water. The purpose of this study was to see the results of photosynthesis reflected in the dry weight due to coconut water in various concentrations. The research was conducted at the Experimental Garden of the Ciparanje Faculty of Agriculture, Jatinangor in October 2018 until March 2019. The experiment used a randomized block design (RBD). The treatments used were several concentrations of coconut water and their combination with inorganic fertilizers. The results showed that the dry weight accumulation of cocoa seedlings was influenced by various concentrations of coconut water, but had no effect on the chlorophyll index. The concentration of coconut water of 50% is the optimum concentration for better dry matter accumulation of cocoa seedlings and can be an alternative fertilizer for cocoa seedlings.